Arthur White Collection. Time Magazine Medicine Article. Test-Tube Baby: Conceived in a laboratory. - unknown, unknown (Time Magazine; Digitized from original print, Valdosta State University Archives and Special Collections, December 8, 2016., 1978)
Time Magazine Medicine article on the test tube baby, parents Lesley and John Brown in Oldham, England in 1978 by doctors Patrick Steptoe (Gynecologist) and Robert Edwards (Physiologist). Article published in 1978.
Test-Tube Baby: Conceived in a laboratory.
Digitized from original print, Valdosta State University Archives and Special Collections, December 8, 2016.
Keywords: Test tube baby; In Vitro Fertilization; IVF; Steptoe-Edwards Fertilization Technique; Time Magazine; Time Magazine Medicine; Time Medicine; Arthur White; Lesley Brown; John Brown; Lousie Joy Brown; Patrick Steptoe; Professor Sir Robert Edwards; Robert Edwards; Oldham General Hospital; Oldham, England; London, England; England; Great Britain; 1970s; 1978